Discrimination between Alkali Metal Cations by Yeast : I. Effect of pH on uptake - Armstrong, W. McD. (The Rockefeller University Press, 1964)
Extracellular pH markedly influences the ability of yeast cells to discriminate between K(+) and Na(+), with K(+) favored to a greater degree at low pH. Studies of the kinetics of uptake of individual alkali metal cations by fermenting yeast indicate three zones relative to pH. Between pH 6 and 8, H(+) has no effect. Below pH 4, H(+) competitively inhibits the transport of each cation. Between pH 4 and 6, H(+) acts kinetically as a predominantly non-competitive inhibitor. Both effects can be reversed by increasing the concentrations of cations. However, the concentrations required to reverse the competitive effect are considerably lower than those required to reverse the apparently non-competitive effect. It is suggested that H(+) and the alkali metal cations can combine with two sites, a transport or carrier site, and a second, non-transporting site that influences the maximal rate of transport. Because the non-competitive inhibitory effect of H(+) is considerably greater on the other cations than on K(+), the discrimination in favor of K(+) is increased severalfold at low pH, beyond that predicted on the basis of the relative affinities for the transport site.